Customer satisfaction and repurchase intention: An application to the telecommunications industry - Cigarra, Cândida Carraça (2012)
In an ever changing world, enterprises need to focus in their customers in order to guarantee their future survival and success. However, what constructs are truly important in determining Customer Repurchase Intention? For a long time, Overall Customer Satisfaction was considered to be the fundamental construct when determining Repurchase Intention. In this study, it is proofed that although Overall Customer Satisfactions is important, it is not the fundamental construct determining Repurchase Intention. Constructs like Quality Perception or Trust play a fundamental role in maintaining a customer, in the complex world of International Telecommunication in a Business to Business perspective.